Defining Community-Based Research - Glenn A. Bowen (The University of Alabama, 2022)
Review of the book: Kerry Strand, Sam Marullo, Nick Cutforth, Randy Stoecker, and Patrick Donohue, Community-Based Research and Higher Education: Principles and Practices. San Francisco: Jossey-Bass, 2003, 304 pages. ISBN: 978-0-7879-6205-0